Pengaruh Model Konseling Behavioral dengan Strategi Self-Management Terhadap Self Order - Widiantari, Ni Luh Putu; Suarni, Ni Ketut; Gading, I Ketut (Universitas Pendidikan Ganesha, 2019)
This study was aimed to know the influence of behavioral counseling model by using self-management strategy toward self-order of grade X students of SMK Negeri 2 Singaraja. The research design used was quasi experimental research in which the design used was post-test only control group design. The population of this study was grade X students of SMK Negeri 2 Singaraja. Furthermore, the sampling technique in this research waspurposive sampling. The data of self-order was collected by using questionnaire method.The collected data was in the form of interval data.Statistic non-parametic test of Mann Whitney test was used to determine whether there was an influence of behavioral counseling method by using self-management toward self-order of the students. The result of the analysis by using Mann Whitney test showed that Z = -3,148 and sig obtained was 0,002. It indicated that significance value obtain was smaller than a in whichit was 0,05 (0,002 < 0,05). Therefore, it could be concluded that â€œthere was an influence of behavioral counseling model by using self-management strategy toward self-order of grade X students of SMK Negeri 2 Singarajaâ€.Â Keywords:Â order, behavioral counseling model, self-management strategy.